The Mode of Sucrose Degradation in Potato Tubers Determines the Fate of Assimilate Utilization - Ferreira, Stephanus J.; Sonnewald, Uwe (Frontiers in Plant Science, 2012)
Cytosolic (U-IN-2) or apoplasmic (U-IN-1) targeting of yeast invertase in potato tubers leads to reduced sucrose and increased glucose, but specific phenotypical changes are dependent on the subcellular targeting of the enzyme. U-IN-2 has a more severe phenotype with the most striking aspects being reduced starch and increased respiration. Despite extensive research, the regulatory mechanisms leading to these changes remain obscure. Technological advancements regarding potato transcriptional and genomic research presented us with the opportunity to revisit these lines and perform detailed gene expression analysis, in combination with metabolic profiling, to identify regulatory networks underlying the observed changes. Our results indicate that in both genotypes reduced UDP-glucose production is associated with a reduced expression of cell wall biosynthetic genes. In addition, U-IN-1 are characterised by elevated expression of senescence-associated genes, coupled to reduced expression of genes related to photosynthesis and the cytoskeleton. We provide evidence that increased respiration, observed specifically in U-IN-2, might be due to sugar signalling via released trehalose-6-phosphate inhibition of the SnRK1 complex. In both genotypes, expression of the plastidic G6P transporter (GPT) is significantly down-regulated, leading to a shift in the cytosolic to plastidic G6P ratio and hence might limit starch synthesis but also the oxidative pentose phosphate pathway. This might explain the observed changes in several additional plastidic pathways, most notably reduced expression of fatty acid biosynthetic genes and an accumulation of shikimate. A strict negative correlation between invertase and GPT expression could be observed in a wide range of potato tubers. This reciprocal regulation may be part of a more general switch controlling energy versus storage metabolism, suggesting that the fate of assimilate utilisation is coordinated at the level of sucrose degradation.